On supergravity and noncritical strings - Andrea Dei; Pietro Ferrero; Leonardo Rastelli (Journal of High Energy Physics)
Abstract Motivated by the long-term goal of finding holographic descriptions for N $$ \mathcal{N} $$ = 1 and N $$ \mathcal{N} $$ = 2 super QCD, we revisit the subject of “noncritical” superstring theory. Focusing on string models with 6d super Poincaré invariance, we provide a careful worldsheet derivation of the leading-order effective theories for the lowest modes. We identify them as seven-dimensional, maximally supersymmetric gauged supergravities: the SO(4) theory for noncritical IIA and the ISO(4) theory for noncritical IIB. The same theories also arise as consistent truncations on S 3 of the 10d IIB and IIA supergravities, respectively, where the chirality flip is as expected from T-duality. These effective supergravities should be interpreted in the following sense. The noncritical string can be viewed as a special case of a discrete series of backgrounds labelled by an integer k (which counts the number of NS5 branes in a certain duality frame); the “noncritical” value is k = 2, while for k → ∞ one recovers a weakly-curved 10d target space. The effective supergravities described here give an accurate description of the interactions among the lowest modes for k → ∞, with higher derivative corrections suppressed by powers of 1/k. We discuss BPS solutions of the 7d gauged supergravities and their uplift to 10d solutions. In particular, we find a novel class of solutions with RR flux, parametrized by a function of three variables that solves an elegant PDE. While we cannot solve the PDE in closed form except in trivial cases, we confirm that our solutions correspond to a 10d IIA Hanany-Witten setup with continuous distributions of both “color” D4 branes and “flavor” D6 branes.